Analisis Pengaruh Motivasi Kerja Terhadap Kinerja Relawan Search And Rescue (BASARNAS) Bandung - Ihsan Dinie Supyaan; Endah Fauziningrum (Master Manajemen, 2023)
Motivation is a state in a person's personality that encourages an individual's desire to carry out certain activities to achieve a goal. It is a person will that manifest to a behavior that is directed in achieving satisfaction goals. This research aims to determine the effect of work motivation on the performance of SAR volunteers at the Bandung National Search and Rescue Agency (BASARNAS). This type of research is quantitative research which using survey method and using t and f testing. The population in this study were all SAR volunteers at the National SAR Agency (BASARNAS). As for the sample was 42 respondents. Data was collected using a questionnaire. The results showed that internal motivation had a significance of 0.126. External motivation has an influence on the performance of volunteers with a significant 0.002. Internal and external motivation together have an influence on the performance of volunteers with a significant 0.008.